Understanding the human-cattle relationship in mountain cow-calf systems: Insights from Spanish farmers - Laura X Estévez-Moreno; Gustavo A María; Pilar Santolaria; Morris Villarroel; Genaro C Miranda-de la Lama (Animal Welfare)
In livestock production, animal welfare is shaped by the quality of the relationship between animals and the farmers with whom they interact. This study investigated the perceptions of Spanish farmers of extensive mountain cow-calf systems regarding the impact of human intervention on animal behaviour, with attention to the human-animal relationship (HAR), farm management strategies, and interactions between animals and unfamiliar people. The research was conducted within the context of cow-calf systems managed under extensive mountain conditions. Seven focus group discussions (FGDs) were conducted, involving 60 mountain cattle farmers from Aragon, Navarra, and the Basque Country. The findings of our study demonstrate that the quality of HAR is contingent upon a multitude of variables, which exert a profound influence on the duration, intimacy, and strength of these relationships, particularly in response to environmental conditions, as reflected, for example, in the changing frequency of human-animal interactions during periods of outdoor grazing compared to times of confinement. Farmers also showed interest in understanding animal behavioural responses in different management scenarios to adapt and individualise their strategies. Across all FGDs, participants recognised the farmer’s role in influencing animals to be less reactive or fearful toward humans through their handling style. Finally, the interactions between people and cows extend beyond farmers and their families, incorporating a variety of unfamiliar individuals who also play a role in each cow’s relationships with humans. Therefore, farmers’ perceptions reveal that animals’ responses to humans are not homogeneous but are highly dependent upon context, ontogeny and levels of familiarity.